Using a multi-task adaptive vr system for upper limb rehabilitation in the acute phase of stroke - Cameirão, Mónica S. (2022)
Nowadays, stroke has become one the main causes of adult disability leading to life-lasting effects, including motor and cognitive deficits. Here we explore the benefits of the use of virtual reality (VR) for the rehabilitation of motor deficits following stroke. We have developed the Rehabilitation Gaming System (RGS), a VR-based apparatus designed for the treatment of the upper extremities. The RGS is a multi-level adaptive system that provides a task oriented training of graded complexity that is online adjusted to the capabilities of the patients. We show results from an ongoing study that evaluates the impact of this system on the recovery of patients in the acute phase of stroke (n=14). The results suggest that the system induces a sustained improvement during treatment, with observed benefits in the performance of activities of daily living.